Cardiovascular magnetic resonance (CMR) normal values for pulmonary arteries in healthy children and adolescents. (8th February 2021) - Boll, C; Voges, I; Caliebe, A; Gati, S; Puricelli, F; Wage, R; Krupickova, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Changes in the right ventricular outflow tract (RVOT) and pulmonary arteries (PAs) are often seen in paediatric patients with congenital heart disease (CHD), pulmonary hypertension or genetic disorders (e.g. Marfan syndrome, Loeys-Dietz syndrome, Williams syndrome, DiGeorge syndrome). Cardiovascular magnetic resonance (CMR) imaging is an excellent method to visualize the RVOT and PAs without the use of ionizing radiation and contrast media but for the interpretation of CMR data in the paediatric population the knowledge of normal values is crucial. However, normal values for pulmonary arteries from contrast-free cine CMR images are lacking. Purpose: The aim of this retrospective multicentre study was to establish reference ranges for the diameters of the mean PA (MPA), right PA (RPA) and left PA (LPA). Methods: 163 CMR scans of healthy children and adolescents (mean age 13.8 ± 2.9 years; range 5-18 years) from two centres in the UK and Germany were included. The diameter of the MPA was measured in sagittal-oblique RVOT cine images and transaxial cine stacks, whereas the diameter of the RPA and LPA were measured from transaxial stacks and specific pulmonary artery branch cine images. Results: Mean systolic and diastolic diameters for the MPA were 22.1 ± 2.8 mm (14.4 ± 2.2 mm/m²)/ 17.2 ± 2.3 mm (11.3 ± 1.9 mm/m²) measured in RVOT cine stacks. Mean systolic and diastolic diameters for the RPA and LPA were:  1) RPA,  12.4 ± 1.7 mm (7, 9 ± 1, 6 mm/m²)/ 9.8 ± 1.6 mm (5.9 ± 1.8 mm/m²) and 2) LPA, 13.3 ± 1.5 mm (8.3 ± 2.1 mm/m²)/ 10.8 ± 1.5 mm (6.8 ± 1.8 mm/m²). Separate centile charts for boys and girls for the MPA were created. Conclusions: We established CMR normal values for the MPA, RPA and LPA for children and adolescents. Our data might be useful for the detection of PA stenosis and dilatation and may serve as a reference in future studies.